Robust control system for Spacecraft Motion Trajectory (European Journal of Pure and Applied Mathematics, 2014)
In aerospace field the economic realization of a spacecraft is one of the main objectives which should be accomplished by conceiving the optimal propulsion system and best control programs. This article focuses on the implementation of uncertain control system theory and development of a robust control system of Spacecraft Motion Trajectory (SMT). The proposed strategy involves the nonlinear mathematical model of SMT expressed in the central field, which is linearized by the Taylor expansion, and model reference Adaptive Control Approach (ACA) with the second Lyapunov method to offer a high rate and unfailing performance in the functioning. The efficiencies of the linearization procedure and the control approach are theoretically investigated through some realistic simulations and tests under Matlab.